Mixed FSO/RF Based Multiple HAPs Assisted Multiuser Multiantenna Terrestrial Communication - Singya, Praveen Kumar; Alouini, Mohamed-Slim (Frontiers in Communications and Networks, 2022)
In this work, a mixed free-space optics (FSO)/radio-frequency (RF) based multiple serial high altitude platforms (HAPs) assisted multiuser multiantenna terrestrial communication system is considered. For the considered multi-hop system, earth station to HAP and HAP to HAP links are assumed as FSO links, and HAP to terrestrial mobile users (MUs) link is assumed as RF link. At the FSO detector both the heterodyne detection and intensity modulation direct detection techniques are considered. Atmospheric turbulence of the ES to HAP FSO link is modeled with Gamma-Gamma fading along with the pointing error impairments. As HAP situates above the stratosphere, negligible atmospheric turbulence exists at HAP altitude (20 km), hence, only pointing error is considered for the inter HAP links. Further, the HAP consists of multiantenna array to provide high data-rates to the terrestrial users via RF links, considered to be Nakagami-m distributed. The intermediate HAPs perform selective decode-and-forward relaying and opportunistic user scheduling is performed for the best user selection. For the performance analysis, analytical expression of overall outage probability is obtained and the impact of various selection parameters like pointing error, FSO detection type, MU selection, number of antennas, and RF fading severity are observed on the outage performance. Asymptotic outage probability is also derived to obtain the diversity order of the considered communication system. Further, considering various modulation schemes, a generalized average bit-error-rate expression is derived and the impact of pointing error, FSO detection type, MU selection, number of antennas, and RF fading severity are observed on its performance. Finally, derived results are validated through Monte-Carlo simulations.